Cognitive-behavioral therapy - Meichenbaum, Donald; Carlson, Jon; American Psychological Association; Governors State University. Center for Extended Learning and Communications Services ([United States] : American Psychological Association, 2007)
Dr. Donald Meichenbaum uses cognitive-behavioral therapy with a constructive-narrative perspective in which he looks at the stories clients tell about themselves and considers ways that the client could develop a different, more positive story
Title from title screen
Moderated by Jon Carlson
Keywords: Cognitive therapy